Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.